REPRESENTASI NILAI-NILAI KARAKTER PADA TOKOH IBU DALAM CERITA RAKYAT “TIMUN MAS” - Dewi Lestari; Helviani Helviani; Heri Isnaini (IKIP Siliwangi, 2018)
This article describes the character's values on the character of Mother named Mbok Rondo in folklore